Comparison between multi-shot gradient echo EPI and balanced SSFP in unenhanced 3T MRA of thoracic aorta in healthy volunteers. Issue 96 (November 2017) - Iyama, Yuji; Nakaura, Takeshi; Nagayama, Yasunori; Oda, Seitaro; Utsunomiya, Daisuke; Kidoh, Masafumi; Yuki, Hideaki; Hirata, Kenichiro; Namimoto, Tomohiro; Kitajima, Mika; Morita, Kosuke; Funama, Yoshinori; et al.
Abstract: Purpose: The purpose of this study was to compare scan time and image quality between magnetic resonance angiography (MRA) of the thoracic aorta using a multi-shot gradient echo planar imaging (MSG-EPI) and MRA using balanced steady-state free precession (b-SSFP). Materials and methods: Healthy volunteers (n = 17) underwent unenhanced thoracic aorta MRA using balanced steady-state free precession (b-SSFP) and MSG-EPI sequences on a 3T MRI. The acquisition time, total scan time, signal-to-noise ratio (SNR) of the thoracic aorta, and the coefficient of variation (CV) of thoracic aorta were compared with paired t -tests. Two radiologists independently recorded the images' contrast, noise, sharpness, artifacts, and overall quality on a 4-point scale. Results: The acquisition time was 36.2% shorter for MSG-EPI than b-SSFP (115.5 ± 14.4 vs 181.0 ± 14.9 s, p < 0.01). The total scan time was 40.4% shorter for MSG-EPI than b-SSFP (272 ± 78 vs 456 ± 144 s, p < 0.01). There was no significant difference in mean SNR between MSG-EPI and b-SSFP scans (17.3 ± 3.6 vs 15.2 ± 4.3, p = 0.08). The CV was significantly lower for MSG-EPI than b-SSFP (0.2 ± 0.1 vs. 0.5 ± 0.2, p < 0.01). All qualitative scores except for image noise were significantly higher in MSG-EPI than b-SSFP scans (p < 0.05). Conclusion: The MSG-EPI sequence is a promising technique for shortening scan time and yielding more homogenous image quality in MRA of thoracic aorta on 3T scanners compared with the b-SSFP.